(untitled) (Journal of the College of Basic Education, 2022)
The interest in testing and measurement methods as means of evaluation in all sports activities gives us a clear and scientific indication of the level of the athlete in these activities based on studies and research and benefiting from other sciences to develop the general level of the game. It is one of the most used evaluation tools, and the importance of the research lies in how to conduct this evaluation process represented by following scientific means in finding an equation deduced to know the degree of effectiveness coefficient of serving performance for advanced players, which facilitates standing at the level of players and knowing their strengths and weaknesses